2016
DOI: 10.1186/s40064-016-2860-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of different conditioning activities on running performance of sprinters

Abstract: This study investigated acute effects of different conditioning activities on sprint performance of collegiate sprinters using a randomized, crossover design. Male sprinters (N = 10; 20.1 ± 0.6 years; 174.6 ± 4.4 cm; 66.7 ± 3.5 kg; 100-m race personal best time, 11.46 ± 0.57 s; means ± SDs) performed two 60-m sprints and one of three treatments within the same day, with an interval of 2 days between the treatments. The baseline sprint was followed by one of three different conditioning activities: mini-hurdles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 13 publications
3
12
1
1
Order By: Relevance
“…Therefore, most studies dealing with the technique of the above 100-m hurdles event are focused on the analysis of kinematics (Ryu & Chang, 2011;Iskra & Coh, 2006;Stein, 2000;Wang & Li, 2000;Salo, Grimshaw, & Marar, 1997;Marar & Grimshaw, 1993;McDonald & Dapena, 1991a;Hücklekemkes, 1990) kinetics (McLean, 1994) and energetic characteristics (Ward-Smith, 1997) of the clearance phase. Moreover, There are few studies examining the effects of external conditions on sprint and hurdle performance (Yoshimoto, Takai & Kanehisa, 2016;Hamlin, Hopkins & Hollings, 2015), and a study examining the effects of early sport specialization on the development of a young athlete (Normand, Wolfe & Peak, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, most studies dealing with the technique of the above 100-m hurdles event are focused on the analysis of kinematics (Ryu & Chang, 2011;Iskra & Coh, 2006;Stein, 2000;Wang & Li, 2000;Salo, Grimshaw, & Marar, 1997;Marar & Grimshaw, 1993;McDonald & Dapena, 1991a;Hücklekemkes, 1990) kinetics (McLean, 1994) and energetic characteristics (Ward-Smith, 1997) of the clearance phase. Moreover, There are few studies examining the effects of external conditions on sprint and hurdle performance (Yoshimoto, Takai & Kanehisa, 2016;Hamlin, Hopkins & Hollings, 2015), and a study examining the effects of early sport specialization on the development of a young athlete (Normand, Wolfe & Peak, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…During the final phase of the shot put, the implement is vigorously pushed up and forward, in which subjects performed shoulder horizontal adduction and elbow extension 26 . Additionally, PAP is more likely to occur if the conditioning activity is specific to the main exercise 27,28 . Therefore, the bench press exercise appears to be a suitable CA to activate PAP mechanisms and improve shot put performance by increasing implement velocity release.…”
Section: Discussionmentioning
confidence: 99%
“…Effective PAPE effects have been reported using different types of conditioning stimulus, such as high resistance loads [6,12,13] or jumping exercises [14]. Although it was previously emphasized that PAPE stimulus is more effective when it is biomechanically similar to the subsequent activity [15], studies using sprints as conditioning stimuli to enhance sprint performance are limited [16,17]. These studies showed that adults did not improve their 60-m sprint speed after 2 × 60 m sprints [16], whereas young male track and field athletes increased their speed in a 100 m sprint after 2 × 20 m resisted sprints, and not after the same sprints as conditioning without resistance [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although it was previously emphasized that PAPE stimulus is more effective when it is biomechanically similar to the subsequent activity [15], studies using sprints as conditioning stimuli to enhance sprint performance are limited [16,17]. These studies showed that adults did not improve their 60-m sprint speed after 2 × 60 m sprints [16], whereas young male track and field athletes increased their speed in a 100 m sprint after 2 × 20 m resisted sprints, and not after the same sprints as conditioning without resistance [17]. It seems therefore that the properties of the conditioning stimulus might be critical for the outcome of the study.…”
Section: Introductionmentioning
confidence: 99%